Identification of a Six Gene Prognosis Signature for Papillary Thyroid Cancer Using Multi-Omics Methods and Bioinformatics Analysis - Ren, He; Liu, Xin; Li, Fuxin; He, Xianghui; Zhao, Na (Frontiers in Oncology, 2021)
Papillary thyroid carcinoma (PTC) is the most common subtype of thyroid cancer. PTC is typically curable with an excellent survival rate; however, some patients experience disease recurrence or death. This study aimed to discover potential key genes and signaling pathways of PTC, which could provide new insights for thyroid lesions. Four GEO microarray datasets were integrated to screen for candidate genes involved in PTC progression. A total of 164 upregulated and 168 downregulated differentially expressed genes (DEGs) were screened. Gene Ontology/ Kyoto Encyclopedia of Genes and Genomes were used in pathway enrichment analyses for DEGs. A protein-protein interaction network was then built and analyzed utilizing STRING and Cytoscape, followed by the identification of 13 hub genes by cytoHubba. CDH3, CTGF, CYR61, OGN, FGF13, and CHRDL1 were selected through survival analyses and shown to play vital roles in tumor progression and the immune system. ROC and K-M plots showed that these genes had good diagnostic and prognostic values for PTC. Finally, GSEA for a single hub gene revealed that candidate hub genes had close associations with PTC development. These findings provide new insights into PTC pathogenesis and helped identify six candidate genes as biomarkers for diagnosis and prognosis of PTC.